Exploring the benefits and disadvantages of introducing synchronous to asynchronous online technologies to facilitate flexibility in learning - Papadima-Sophocleous, Salomi; Loizides, Fernando (My University, 2016)
This article examines the impact of online synchronous tutorials on eight second language (L2) practitioners enrolled in a Master of Arts (MA) in ComputerAssisted Language Learning (CALL) L2 Curriculum Development and Evaluation module. The module is delivered asynchronously and synchronously (lecture). To accommodate immediate interaction to the instructor and the students, weekly synchronous online tutorials were also included. These tutorials aimed to give the opportunity to learners to get their questions answered immediately and receive instant feedback, reinforce their understanding of the content covered and the assigned tasks, discuss issues of concern, share ideas and knowledge, and interact with the instructor for questions or problems. A mixed-method data collection approach was used (records of student participation, online interviews in the middle of the course and online interviews at the end of the 13-week module). The data analysis indicated a positive attitude towards tutorials, improvement in clarity in participants’ understanding of the material studied and development of a sense of comfort and reassurance.
Keywords: E-learning; Online synchronous tutorials; CALL teacher-training